Antidiabetic and In Vitro Enzyme Inhibition Studies of Methanol Extract of Ocimum tenuiflorum Linn Leaves and Its Fractions - Leila Mousavi; Rabeta Mohd Salleh; Vikneswaran Murugaiyah (Tropical Life Sciences Research, 2020)
The current study aimed to determine the best dose of methanol extract of Ocimum tenuiflorum L. leaves extract, and it is a fraction to blood-glucose-lowering in diabetic rats, and evaluated the ?-amylase, ?-glucosidase inhibitors and insulin level of diabetic rats used to achieve greater control over hyperglycemia. The result of the antihyperglycaemic of oral administration of a different dose of methanol extract in streptozotocin-induced rats showed that the highest dose of methanol extract significantly reduced the blood glucose level compared to another dose. Also, the result of repeated administration of methanol fractions indicates that ethyl acetate-butanol fraction exhibited a stronger antihyperglycemic effect than chloroform and ethanol-water fractions. Moreover, the result showed that effect of methanol extract and its fraction on ?-glucosidase and ?-amylase enzymes activities and its insulin level by in vitro study, ethyl acetate-butanol fraction could control with low concentration compared to other fractions and acarbose that used as a positive control. From the result of insulin level, methanol extract and fraction did not show any significant. These findings indicated that the active crude extract (methanol) and its active fractions (ethyl acetate/butanol) could exert significant glucose-lowering effect due to the presence of polyphenolics active constituents. In conclusion, isolation of the active components of Ocimum tenuiflorum L. may pave the way to the development of new agents for the treatment of diabetes and its complications.